The philosophy of science : a contemporary introduction - Rosenberg, Alexander, 1946-; McIntyre, Lee C. (Routledge, 2020)
"Any serious student attempting to better understand the nature, methods, and justification of science will value Alex Rosenberg's and Lee McIntyre's updated and substantially revised Fourth Edition of Philosophy of Science: A Contemporary Introduction. Weaving lucid explanations with clear analyses, the volume is as a much-used, thematically-oriented introduction to the field"--